The Degree of school Principals Acquiring of educational technology competencies and its relation to teacher application of education technology from teachers point of view - Banisaeed, Kawthar Mohammad Rasheed (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the degree of school principals acquiring of educational technology competencies and its relation to teacher implementation of education technology from teachers point of view, the study used the descriptive analysis correlative approach, two questionnaires were development first one consisted from (20) paragraph, to determine the school principals acquiring of educational technology competences, the second also consisted from (20) paragraph to determine the teacher implementation of education technology , the sample of study consisted from (340) female and male teacher. However, the finding of study showed that the school principals acquiring of educational technology competencies from teacher point of view was average and the teacher implementation of education technology from teacher point of view was also average, the finding also showed there was a statistically significant relationship between the school principals acquiring of educational technology and teacher implementation of them at the level of (α ≤ 0.05). In addition, the finding showed there weren’t any significant relation in the degree of school principals acquiring of educational technology competencies from teacher point of view refers to variable of teacher's sex. Furthermore, there were significant differences at (α ≤ 0.05) according to teacher qualification for higher education.
Keywords: educational technology competences; school principals; Ajloun Directorate